Volume 5: Structures and Dynamics, Parts a and B 2008
DOI: 10.1115/gt2008-50538
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Unsteady Flow Phenomena in a Partial Admission Axial Steam Turbine

Abstract: This paper presents a numerical investigation of unsteady flow phenomena in a two-stage partial admission axial steam turbine. Results from unsteady three-dimensional computations are analyzed and compared with the available experimental data. Partial admission in the present study is introduced into the model by blocking only one segmental arc of the inlet guide vanes. Blocking only one segment (which corresponds to the experimental setup) makes the model unsymmetrical; therefore it is necessary to model the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…(1) Non-uniform intake imposes bending and radial moments on the rotor, which may result in rotor vibrations [6][7][8] and even faults [9], thus affecting bearing safety [10]; (2) Non-uniform intake causes mixed loss in the cascade channel [11][12][13][14] or blast loss [15,16], and a mismatch between the chamber outlet airflow angle and the geometric angle of the first stage static cascade causes shock loss [17]; (3) Non-uniform intake causes an increase in the amplitude of airflow excitation forces on the first-stage dynamic and static lobes [18] and complex excitation force frequencies [5,13,[19][20][21][22].…”
Section: Figurementioning
confidence: 99%
“…(1) Non-uniform intake imposes bending and radial moments on the rotor, which may result in rotor vibrations [6][7][8] and even faults [9], thus affecting bearing safety [10]; (2) Non-uniform intake causes mixed loss in the cascade channel [11][12][13][14] or blast loss [15,16], and a mismatch between the chamber outlet airflow angle and the geometric angle of the first stage static cascade causes shock loss [17]; (3) Non-uniform intake causes an increase in the amplitude of airflow excitation forces on the first-stage dynamic and static lobes [18] and complex excitation force frequencies [5,13,[19][20][21][22].…”
Section: Figurementioning
confidence: 99%
“…Sakai established a partial admission quasi-three-dimensional numerical model of steam turbine, and analyzed the influence of inlet steam's position on the turbine's efficiency [20]. Hushmandi presented a three-dimensional numerical model of steam turbine with asymmetric inlet steam, and found that the static pressure in the governing stage in circumferential direction change significantly in the case of partial admission, which resulted in a great instability force on rotor and blades [21]. In addition, Jeffrey calculated the amount of seal leakage, rotor dynamic coefficients as well as the steam exciting force by using a three-dimensional model [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…According to Wlassow et al, 2 entropy generation is mainly caused by turbulent dissipation and facilitates identifying reduced efficiency in cases of cooling because, as an additional entropy production, the cooling flow mixes with the mainstream. The influence of the stator-rotor hub gap sealing flow was studied by Reid et al 3 Hushmandi et al 4 conducted numerical research on unsteady flow in a two-stage partial admission axial steam turbine and analysed entropy generation at different cross sections, which indicate that while travelling to the downstream stages, the peak entropy moves in a tangential direction. Mansour et al 5 reported unsteady entropy measurements in an axial turbine.…”
Section: Introductionmentioning
confidence: 99%